Prognostic Significance of Blood Transfusion in Newly Diagnosed Multiple Myeloma Patients without Autologous Hematopoietic Stem Cell Transplantation. (8th May 2017) - Fan, Liping; Fu, Danhui; Zhang, Jinping; Huang, Haobo; Wang, Qingqing; Ye, Yamei; Xie, Qianling
Abstract : The aim of this study was to evaluate whether blood transfusions affect overall survival (OS) and progression-free survival (PFS) in newly diagnosed multiple myeloma (MM) patients without hematopoietic stem cell transplantation. A total of 181 patients were enrolled and divided into two groups: 68 patients in the transfused group and 113 patients in the nontransfused group. Statistical analyses showed that there were significant differences in ECOG scoring, Ig isotype, platelet (Plt) counts, hemoglobin (Hb) level, serum creatinine (Scr) level, and β 2 -microglobulin (β 2 -MG) level between the two groups. Univariate analyses showed that higher International Staging System staging, Plt counts < 100 × 10 9 /L, Scr level ≥ 177 μ mol/L, serum β 2 -MG ≥ 5.5 μ mol/L, serum calcium (Ca) ≥ 2.75 mmol/L, and thalidomide use were associated with both OS and PFS in MM patients. Age ≥ 60 was associated with OS and Ig isotype was associated with PFS in MM patients. Moreover, blood transfusion was associated with PFS but not OS in MM patients. Multivariate analyses showed that blood transfusion was not an independent factor for PFS in MM patients. Our preliminary results suggested that newly diagnosed MM patients may benefit from a liberal blood transfusion strategy, since blood transfusion is not an independent impact factor for survival.